Ethnobotanical Study of Medicinal Plants in Kazeroon, Iran: Identification, Distribution and Traditional Usage - M Dolatkhahi; M Ghorbani Nohooji; A Mehrafarin; GR Amini Nejad; A Dolatkhahi (Institue of Medicinal Plants, ACECR, 2012)
Background: Kazeroon, with about 4060 km², is situated in the west of Shiraz (Fars province). This region is an important area which shows a great plant biodiversity. Also this ancient region is one of the most important human migration roads in Iran and so traditional usage of medicinal plant is a familiar therapeutic way for native people. Objective: The traditional usages of the medicinal plants of region were focused and therefore some beneficial information was gathered using native people questioning. Methods: Medicinal plant flora of region was studied during 2007-2009. All ancient villages were discovered using various geographical maps and then the vernacular information of plants and their usages were collected from well experienced people and finally the collected plants were identified scientifically. Results: 91 species (87 genera and 39 families) were reported from the rangelands around the Kazeroon. Lamiaceae, with 11 species, and Asteraceae with 9 species were the largest families respectively, and Plantago (Plantaginaceae) with 3 species was the largest genus in the medicinal flora of area. Conclusion: Medicinal plant species are used mainly in remediation of Digestive, Blood Transfer and Urinary system diseases respectively. Studied region shows high degree of species richness and its people are familiar with medicinal plants use. Therefore these traditional and local medicinal usage information of plants are more important and useful for future farmacological investigations.